2009
DOI: 10.1021/jp810020p
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cytoplasm Electrolyte Concentration on Maxwell−Wagner Polarizability of Bacteria E. coli

Abstract: The electric polarizability of bacteria is considered in the literature to have a surface charge dependent (ChD) and a Maxwell-Wagner (MW) mechanism. We distinguish experimentally both the types of interface polarizability by the frequency of the electric field and the medium electrolyte concentration. It was shown in a previous work ( Zhivkov , A. M. ; Gyurova , A. Y. Colloids Surf., B 2008 , 66 , 201. ) that the ChD component is shown up on the outer bacteria surface even at megahertz frequencies. The MW pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…It was shown that the ionic flow through the ethanol treated membrane is not able to change significantly the outer electrolyte concentration at our experimental conditions and therefore the magnitude of EChD component remains almost constant [14]. This means that the decrease in the difference between the values of polarizability in absence and in presence of 10 vol.% ethanol with the increase in the electrolyte concentration is not related to an additional decrease in EChD component except that resulting from the presence of KCl.…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…It was shown that the ionic flow through the ethanol treated membrane is not able to change significantly the outer electrolyte concentration at our experimental conditions and therefore the magnitude of EChD component remains almost constant [14]. This means that the decrease in the difference between the values of polarizability in absence and in presence of 10 vol.% ethanol with the increase in the electrolyte concentration is not related to an additional decrease in EChD component except that resulting from the presence of KCl.…”
Section: Resultsmentioning
confidence: 56%
“…The estimation of the inner electrolyte concentration showed that it is high enough and therefore IChD component practically does not exhibit. That let us to conclude that IMW component has the main contribution on the inner membrane surface at the frequency range mentioned above [14].…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations